Participation of Indigenous Papuan Women at the Skouw Border Market, Indonesia–PNG - Kristien Maryen; Yakoba Womsiwor; Claudia Conchita Renyoet (Cenderawasih University, 2021)
This article aims to scrutinize the extent of participation of Indigenous Papuan Women in the Skouw Border Market and the challenges they encounter. The Skouw market contributes to Indonesia’s economic development where Indigenous Papuan traders and Nusantara traders (non-Papuans) are the drivers. This study adopted qualitative research, while primary and secondary data were collected through interviews, observations, and library research. By using an Indigenous feminism approach, this article demonstrates several points: 1) the participation of indigenous Papuan women in the Skouw market is pretty deficient compared to Nusantara traders, thereby providing guidance and initial capital from the government to enable Papuan women is required; 2) commodities sold by Indigenous Papuan women should be expanded – not only focusing on farming products but need to sell commodities similar to those of Nusantara traders; 3) if indigenous Papuan women continue to face marginalization and get limited access to the Skouw market, this could be seen as a new form of colonization for Papuan women. KEYWORDSIndigenous; Indonesia; Papua; PNG; Skouw